Successful treatment with HLA-matched peripheral hematopoietic stem cell transplantation for very severe hepatitis-associated aplastic anemia complicated with multidrug-resistant bacterial and fungal infections: A case report - Li, Hua; Li, Xiaofan; Chen, Xianling; Li, Nainong (Frontiers in Pediatrics, 2022)
Hepatitis-associated aplastic anemia (HAAA) is a life-threatening hematologic disorder characterized by bone marrow failure. Allogeneic hematopoietic stem cell transplantation (HSCT) is the first-line treatment for HAAA. Severe infection and complications in patients with very severe aplastic anemia are the challenges to the efficacy of HSCT. We report a rare case of successful transplantation with HLA-matched peripheral hematopoietic stem cells for a 15-year-old girl suffering from HAAA with multidrug-resistant bacterial and fungal infections. Through effectively controlling infection and optimal timing of transplantation by adjusting the conditioning regimen, the allo-HSCT was successfully performed for the patient. Updated data of following-up 26 months after transplantation showed that the patient was still in complete remission with a good quality of life. This case provided a reference for treating severely infected patients with HAAA before HSCT.